Թիֆլիսում ՀՀ դիվանագիտական ներկայացուցչության վերաբերմունքը 1919 թ. վրաց-ադրբեջանական ռազմաքաղաքական դաշինքի նկատմամբ - Ղազարյան, Արտակ
Позиция Армении была сбалансирована с грузино-азербайджанским военно-политическим союзом. И правительство Армении и дипломатическое представительство Армении в Тифлисе, исходя из интересов Армении в Тбилиси, предпочли принять ситуационные решения и не испортить отношения со всеми странами, в том числе Деникиным. Вот почему Армения поддерживала сбалансированный нейтралитет и не присоединилась к грузино-азербайджанского военно-политического блока, который был подписан 16 июня 1919 года. The position of Armenia was balanced against the Georgian-Azerbaijani military-political alliance, and at the moment when the Armenian government and the Armenian diplomatic representation in Tiflis, based on Armenia's interests in Tbilissi, preferred to make situational decisions and not to spoil relations with all countries, including Denikin. That is why Armenia maintained a balanced neutrality and did not join the Georgian-Azerbaijani military-political bloc, which was signed on June 16, 1919.
Keywords: Պատմություն